A Test of Generalizability of the Social Development Model Across Gender and Income Groups with Longitudinal Data from the Elementary School Developmental Period - Fleming, Charles B. (Journal of quantitative criminology, 2002)
The social development model (SDM) is a theory of behavior that has proven useful in explaining the etiology of delinquency, violence, and substance use among adolescents as well as early antisocial behavior among pre-adolescents. A further test of the model is its generalizability across population groups. A section of the SDM representing prosocial influences in the etiology of problem behavior was compared for boys and girls and for children from low- and non low-income families using three waves of child, parent and teacher survey data on a sample of 851 elementary school students. Multiple group structural equation modeling was used to assess differences across groups in both measurement of model constructs and hypothesized structural paths between constructs. The results indicate overall similarity in the reliability of measurement models and validity of structural models.